OP35 A process evaluation of the social and emotional education and development trial: case study findings. (September 2018) - Tweedie, S; Smillie, S; Wight, D; Elliott, L; Purcell, C; Haw, S; Bond, L; Henderson, M
Abstract : Background: The Social and Emotional Education and Development programme (SEED) aims to improve the social and emotional wellbeing (SEW) of primary school pupils. It is based on a cycle of collecting school specific data on pupil and staff SEW, providing benchmarked feedback and facilitating the adoption of evidence-based initiatives to address need. A stratified randomised controlled trial (RCT) involved 37 schools across three local authority districts in Scotland between 2013 and 2017. Complementing the RCT was a detailed process evaluation, which enabled interpretation of the trial outcomes and answered secondary questions on implementation, mechanisms and context. We present the first stage of the process evaluation, an assessment of the likely effectiveness of the intervention prior to knowing the quantitative outcomes of the trial, focusing on case study schools. Methods: The process evaluation design was guided by the UK Medical Research Council framework for the evaluation of complex interventions. Mixed methods included semi-structured interviews with head/depute head teachers and educational psychologists, ethnographic notes from reflexive discussion sessions, focus groups with pupils and staff, pupil and parent questionnaires. The preliminary analysis was carried out on ten case study schools. Results: SEED was delivered largely as intended, the main exception being fewer reflexive discussion and action cycles than intended. Participants cited restrictions on time and resources and a lack of embeddedness in local authority structures as barriers to implementation. There was evidence that SEED was valued for providing time and structure to reflect on SEW and foster a collective commitment to tackle and prevent problems, although actions often reinforced existing priorities rather than encouraged the adoption of innovative initiatives. There was limited evidence of an improvement in pupils' SEW but there was evidence that SEED improved relationships between staff. The school's pre-existing climate, strength of leadership and readiness for change appeared important in determining engagement with SEED. Conclusion: Based on this preliminary case study analysis we were not confident that enough schools implemented the intervention in sufficient depth to demonstrate an effect on pupils' Strengths and Difficulties Questionnaire scores (primary outcome). However, the RCT subsequently found a significant improvement in pupil SEW across the life of the trial, particularly for older pupils. Ongoing process evaluation analyses aim to explain this and revisit key questions of implementation and mechanisms for change. These analyses will be available by September 2018.